Volume 2A: Turbomachinery 2016
DOI: 10.1115/gt2016-56682
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity Dynamics Based Flow Diagnosis for a 1.5-Stage High Pressure Compressor With an Optimized Transonic Rotor

Abstract: This paper presents an optimized rotor as part of a 3-blade row optimization (IGV-rotor-stator) of a high-pressure compressor. It is based on modifying blade angles and advanced control of curvature of the airfoil camber line. The effects of these advanced blade techniques on the performance of the transonic 1.5-stage compressor were calculated using a 3D Navier-Stokes solver combined with a vortex/vorticity dynamics diagnosis method. The optimized rotor produces a 3-blade row efficiency improvement over the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Further, these techniques were extended in Li et al 28 to account for three-dimensional viscous flow in axial compressor leading again to an improved rotor design. The recent study of Chen et al 29 also utilized x y as one of the two parameters to analyze the flow field through an optimized transonic rotor. These studies are for uniform inlet flows, and it remains to be seen how the non-uniform vorticity field is modified due to and through the compressor.…”
Section: Total Pressure Lossmentioning
confidence: 99%
“…Further, these techniques were extended in Li et al 28 to account for three-dimensional viscous flow in axial compressor leading again to an improved rotor design. The recent study of Chen et al 29 also utilized x y as one of the two parameters to analyze the flow field through an optimized transonic rotor. These studies are for uniform inlet flows, and it remains to be seen how the non-uniform vorticity field is modified due to and through the compressor.…”
Section: Total Pressure Lossmentioning
confidence: 99%
“…Some researchers have attempted to characterize the turbulence in a tip-leakage flow of a single blade using non-linear RANS and zonal LES, as shown by Monier et al [24]. While Chen et al [25,26] demonstrated the vorticity dynamics-based flow diagnosis for a 1.5 stage high-pressure compressor using RANS simulations to improve compressor aerodynamic performance, Wu and Porté-Agel [27] presented the atmospheric turbulence effects on wind turbine wakes using LES. While these studies employed LES, Siddappaji [28] demonstrated TKE is equal to viscous dissipation using momentum, vorticity, and entropy transport through RANS simulations in adiabatic process with an in-house analysis framework.…”
Section: Introductionmentioning
confidence: 99%
“…According to Newton's law, in a coordinate system tangential and normal to the streamline, the resulting equations are shown in Figure 1 (assuming inviscid flow) [22] [23]. The static pressure gradient normal to the streamline is balanced by the density times velocity squared divided by the streamline radius of curvature, R. It shows that it is vital to skillfully control streamline curvature in a design process, since pressure gradient of the fluid is influenced significantly by streamline curvature.…”
Section: Pressure Gradient and Curvaturementioning
confidence: 99%